Recasting and Redefining the Notion of Local Democracy in Thailand - Promgird, Pornamarin; Singkaneti, Banjerd; Sririn, Warunya (King Prajadhipok’s Institute Journal, 2024)
The concept of modern local democracy aims to empower people by decentralizing power from the central government to local communities while ensuring that individuals within these communities have the right to demand that their preferences are met as fully as possible. The belief is that local democracy will increase more political participation among the populace. When people become engaged in politics, they will become more active, develop a sense of citizenship, gain confidence in their political efficacy, and participate in local development independently. In Thai society, when addressing decentralization and local democracy, there is still a tendency to limit the scope of meaning to only the election of the local administrative committee. Moreover, administration within local government organizations has not yet fully aligned with the principles of democratic self-government, which seek to expand the base of direct political participation at the local community level as much as possible. This article proposes to recast and redefine the meaning of local democracy in Thailand to follow the democratic path and help strengthen local communities.